Body composition and performance of high-ranking female athletes of Mongolia - Shagdar, Bat-Erdene; Galsan-Yondon, Sukhbat; Sundui, Enebish; Agvaandaram, Gurbadam (Proceedings of the Mongolian Academy of Sciences, 2023)
The purpose of this study is to determine the level of morphological and functional indicators depending on sports specializations among distinguished Mongolian female athletes. Our study involved 123 athletes aged 18-34 in six sports disciplines and the body composition of the athletes were measured by anthropometry and bioelectrical impedance. Physical performance was assessed by Harvard Step Test, alongside spirometry and physical fitness tests. Sports specializations affect the indicators of physical development and body composition of athletes, which revealed significant differences between them. According to the Harvard Test, 85% (34) of team sports athletes, 53.4% (31) of martial arts athletes received good and excellent marks. High-ranking Mongolian male athletes have different body compositions according to various sports disciplines and one can create a profile of an athlete within specific sports. Many years of training can improve an athlete’s performance. The cardiovascular function of athletes involved in martial arts quickly returns to normal after training.